Warisan Metafora Ahmad Syafii Maarif - Putra, Heru Joni (MAARIF Institute, 2023)
This article is the earliest exploration of the legacy of metaphors created by Ahmad Syafii Maarif in his writings. As an initial exploration, this article discusses three examples of the many metaphors contained in the two books of his latest collection of writings, namely Indonesia Approaching a Century: Reflections on Community, Nationality and Humanity (Mizan, 2022) and Bullets of Reflections on the Mujahid (Publisher Kompas Books, 2023). The three metaphors chosen are both related to the existence of the state, especially the nation, politics and republic. However, the three of them are different from each other, not only in context but also in the structure of the metaphor itself. Furthermore, as an intellectual product from a seasoned scholar, this article also tries to display the initial potential of these three metaphors as Cultural Memory, so that the legacy of these metaphors in the future will not only be positioned as the result of linguistic skill but can also become a means to ignite awareness. collective.